2011
DOI: 10.1007/s00415-011-5950-z
|View full text |Cite
|
Sign up to set email alerts
|

Dyslipidaemia in chronic acquired distal axonal polyneuropathy

Abstract: The link between hypertriglyceridaemia (HTG) and/or hypercholesterolaemia (HCL) and neuropathy is uncertain. We retrospectively reviewed records of 100 consecutive patients investigated for acquired chronic axonal distal polyneuropathy of unknown cause. Findings were compared with those of 102 consecutive controls. Patients with idiopathic neuropathy were subsequently compared with age-and gender-matched controls. There were more neuropathy patients than controls with HCL, defined as cholesterol levels [5 mmol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 19 publications
0
10
0
1
Order By: Relevance
“…Another controlled study found no difference in fasting cholesterol levels in patients with CIAP, but increasing fasting triglycerides level was significantly associated with the likelihood of CIAP after adjusting for BMI, age, and gender (30). A recent, small, controlled study did not demonstrate a significantly higher frequency of dyslipidemia or fasting cholesterol level, but fasting triglycerides level was borderline nonsignificantly lower in patients with idiopathic neuropathy (31). The divergent observations could be explained by markedly higher fasting triglycerides levels in patients and lower levels in controls in the former study when compared with patients and controls in the latter study and our study (30,31).…”
Section: Discussionmentioning
confidence: 88%
“…Another controlled study found no difference in fasting cholesterol levels in patients with CIAP, but increasing fasting triglycerides level was significantly associated with the likelihood of CIAP after adjusting for BMI, age, and gender (30). A recent, small, controlled study did not demonstrate a significantly higher frequency of dyslipidemia or fasting cholesterol level, but fasting triglycerides level was borderline nonsignificantly lower in patients with idiopathic neuropathy (31). The divergent observations could be explained by markedly higher fasting triglycerides levels in patients and lower levels in controls in the former study when compared with patients and controls in the latter study and our study (30,31).…”
Section: Discussionmentioning
confidence: 88%
“…Therefore, a direct causal link between CIP and increased total cholesterol levels probably is non-existent. However, the role of lipid metabolism is a matter of controversial discussion [37]. …”
Section: Discussionmentioning
confidence: 99%
“…They did not report an association with triglycerides, but it must be noted that their cohort with ISFN had higher mean triglycerides. Rajabally and colleagues reviewed retrospectively the records of 100 consecutive patients investigated for acquired chronic axonal distal polyneuropathy and found that mean triglyceride levels in patients with chronic idiopathic axonal polyneuropathy were comparable to those of controls . However, hypertriglyceridemia was significantly more common ( P = 0.027), and triglyceride levels were significantly higher ( P = 0.005) in patients with neuropathy due to diabetes/IGT/alcoholism than in patients with neuropathy of any other cause …”
Section: Discussionmentioning
confidence: 99%
“…Recently there has been evidence to suggest a link between hypertriglyceridemia and development of distal sensory neuropathy . In a prospective and well controlled investigation into the etiology of chronic idiopathic axonal polyneuropathy (CIAP) presenting with symptoms to a specialist Neurology clinic, Hughes et al reported higher mean triglyceride concentrations in patients than controls .…”
mentioning
confidence: 99%